Pengaruh Work Engagement, Work Life Balance dan Work Overload terhadap Produktivitas Kerja Pegawai di Dinas Koperasi Perdagangan dan Perindustrian Kabupaten Asahan - Grace Ananda Situngkir; Abdul Rahman (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examined the effect of work engagement, work-life balance, and work overload on employee work productivity at the Cooperative, Trade, and Industry Office of Asahan Regency. The research was motivated by declining institutional performance, increasing workload, and challenges in maintaining employee productivity within the public sector. A quantitative approach was employed using a saturated sampling technique involving all 40 employees as research respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The findings revealed that work engagement did not significantly affect employee productivity. In contrast, work-life balance and work overload had positive and significant effects on work productivity. Simultaneously, the three independent variables significantly influenced employee productivity with an R-square value of 0.547, indicating that 54.7% of productivity variation could be explained by the model, while the remaining 45.3% was influenced by other factors outside the study. The results indicate that maintaining work-life balance and managing workload effectively are important factors in improving employee productivity in government institutions.